2021
DOI: 10.1101/2021.09.03.458884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Immunomodulatory Effects of Social Isolation in Mice are Linked to Temperature Control

Abstract: Living in isolation is considered an emerging societal problem that negatively affects the physical wellbeing of its sufferers in ways that we are just starting to appreciate. This study investigates the immunomodulatory effects of social isolation in mice, utilising a two-week program of sole cage occupancy followed by the testing of immune-inflammatory resilience to bacterial sepsis. Our results revealed that mice housed in social isolation showed an increased ability to clear bacterial infection compared to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 158 publications
0
1
0
Order By: Relevance
“…Consequently, a recreation of this condition in mice is counterbalanced with vaccination (Wu et al, 2018). Other authors found that social isolation primed the immune system of isolated mice for infection allowing them to clear bacterial threats more effectively than grouped mice (Hamilton et al, 2022). Thus, housing conditions could be a key variable to understand fluctuations in NSC activity through immune system modification.…”
Section: How Social Living Conditions Affect Neurogenesismentioning
confidence: 99%
“…Consequently, a recreation of this condition in mice is counterbalanced with vaccination (Wu et al, 2018). Other authors found that social isolation primed the immune system of isolated mice for infection allowing them to clear bacterial threats more effectively than grouped mice (Hamilton et al, 2022). Thus, housing conditions could be a key variable to understand fluctuations in NSC activity through immune system modification.…”
Section: How Social Living Conditions Affect Neurogenesismentioning
confidence: 99%